THE EFFECT OF THE COVID-19 PANDEMIC ON THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN GHANA - Musah, Alhassan; Padi, Abigail; Ahmed, Ibrahim Anyass (International Journal of Accounting & Finance Review, 2022)
This study examines the effect of the covid-19 pandemic on the profitability of commercial banks in Ghana. The study sampled 24 commercial banks over a 5-year study period from 2017 to 2021. The study collected data from the annual report of these banks. The study measured bank profitability using return on assets and return on equity. The main dependent variable was the covid-19 pandemic, measured as a dummy variable. The study relied on descriptive statistics, correlation analysis, and panel regression analysis to realize the research objectives. The correlation analysis, as well as the panel regression analysis, revealed that there is a positive coefficient between covid-19 pandemic and the return on assets of commercial banks in Ghana. The positive coefficient between covid-19 pandemic and return on assets is statistically significant at a 1% significance level which implies that covid-19 is a significant determinant of the increase in return on assets among commercial banks in Ghana. The correlation and panel regression analysis showed a positive relationship between covid-19 pandemic and returned on equity. However, the positive relationship between covid-19 pandemic and return on equity is not statistically significant, implying that the covid-19 pandemic is not a significant predictor of the changes in return on equity among commercial banks in Ghana. JEL Classification Codes: E44, G21, G41, E59, G01, G10, G29, L10.